Analysis of Judge’s Considerations in Decision Number 1441/Pid.Sus/2019/PN Mks Alleged Case of Malpractice Reviewed from Law Number 17 of 2023 - Denta Lufy Nur Yandini; M. Junaidi (Universitas Muhammadiyah Surakarta, 2025)
Medical malpractice is an error by medical personnel that violates the code of ethics and standards of procedure, while negligence is an accident in medical action, with both having the potential to cause harm to patients, so that legal and medical professional regulations require informed consent and regulate criminal liability for violations of professional standards and negligence. The purpose of this study is to explain related to the analysis of the judge's consideration in Decision Number 1441/Pid.Sus/2019/PN Mks in review of Law Number 17 of 2023. By using a normative juridical method with a case study of Decision Number 1441/Pid.Sus/2019/PN Mks and a descriptive approach to reveal and explain the criminal act of medical personnel malpractice in a legal perspective supported by literature study data sources. The results of this study are Decision Number 1441/Pid.Sus/2019/PN Mks acquitting the defendant because the element of negligence in Article 360 paragraph (1) of the Criminal Code was not proven legally and convincingly. Administrative violations, such as the absence of certification and written informed consent, are considered more appropriately handled ethically and administratively. The judge applied the principle of in dubio pro reo and assessed medical complications as a risk of medical action, not the fault of the defendant. This verdict emphasizes that law enforcement must consider medical professionalism, procedural standards, and the principle of justice without conviction without strong evidence.